2009
DOI: 10.1080/10428190902789181
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin and curcumin induce apoptosis in primary resting B chronic lymphocytic leukemia cells

Abstract: B chronic lymphocytic leukemia (B-CLL) cells exist in patients as slowly accumulating resting as well as proliferating B cells. In this study, we examined whether Rapamycin and Curcumin, two naturally occurring compounds shown to have apoptotic effects, could selectively induce apoptosis in resting B-CLL cells. Mononuclear cells isolated from patients with B-CLL were treated with these agents and analysed by AnnexinV/propidium iodide binding, caspase activity, and changes in bcl-2/Bax ratio. Rapamycin and curc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Curcumin exhibits cancer growth inhibition both in vitro and in vivo [5,6]: it suppresses cell proliferation in a variety of cancer cell lines and it inhibits tumorigenesis [7][8][9][10][11][12][13][14][15][16][17]. Multiple mechanisms of action are likely responsible for Curcumin various effects on cancer cells: G1/S arrest and apoptosis induction have been observed other than the mitotic block in different tumor cell lines [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin exhibits cancer growth inhibition both in vitro and in vivo [5,6]: it suppresses cell proliferation in a variety of cancer cell lines and it inhibits tumorigenesis [7][8][9][10][11][12][13][14][15][16][17]. Multiple mechanisms of action are likely responsible for Curcumin various effects on cancer cells: G1/S arrest and apoptosis induction have been observed other than the mitotic block in different tumor cell lines [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other studies recently reported a pro-apoptotic effect of rapamycin in primary B-CLL cells, thereby emphasizing the therapeutic value of mTOR inhibition in this disease. 90,91 Finally, Zanesi and colleagues showed the ability of rapamycin to improve survival of CLL transgenic mouse. 92 Given these results, clinical trials are ongoing in CLL and results from two phase II clinical trials have been recently published.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…However, single-isoform inhibitors against PI3Ka/b/d and pan-class-1 PI3K inhibitors in CLL cells have all been reported to induce apoptosis. 22,23 Pharmacologic inhibition of mTOR induces cell cycle arrest and apoptosis in CLL cells [24][25][26] ; however, prolonged inhibition of mTOR is known to disrupt negative feedback loops and cause increased AKT S473 activation in other malignancies. 27,28 Given the important role of both PI3K and mTOR in CLL cell survival, the dual pharmacologic inhibition of both class-1 PI3K and mTOR signaling may offer new therapeutic potential, with the possibility of deeper remissions or as an alternative after resistance to idelalisib.…”
Section: Cd19mentioning
confidence: 99%